Corruption, Bureaucratic Failure and Social Policy Priorities. (October 2013) - Dahlström, Carl; Lindvall, Johannes; Rothstein, Bo
This article argues that bureaucratic capacity – the competence and reliability of the national bureaucracy – matters to the allocation of public spending among welfare state programmes since it is difficult for governments to justify high levels of spending on programmes that require bureaucrats to make case-by-case decisions, on a discretionary basis, if the bureaucracy is incompetent, corrupt or both. We expect bureaucratic capacity to have a positive effect on programmes that involve bureaucratic discretion, but weak or no effects on programmes that are more straightforward to implement. In order to test these hypotheses, we analyse public spending on active labour market programmes (which involve a lot of discretion) and parental leave benefits (which involve less discretion). Relying on data for twenty advanced democracies from the mid-1980s to the mid-2000s, we find that high bureaucratic capacity does have a positive effect on active labour market policy spending, but not on parental leave benefits.